(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Hepatitis B virus presents a major problem as an occupational risk to healthcare workers (HCWs) in Pakistan, where the vaccination coverage rates do not reach the optimal levels despite the availability of an effective vaccine. Purpose: The aim of the study is to identify the status of HCWs vaccinated against hepatitis B in three large tertiary care hospitals across Peshawar and further assess knowledge, perceptions, work-related variables, and obstacles to vaccination. Materials and Methods: The study is a descriptive cross-sectional study that was carried out between May, 2024 to September, 2024. After conducting informed consent, actually 300 HCWs (doctors, nurses, technicians) of three tertiary hospitals of Peshawar were interviewed face to face using structured questionnaire. Descriptive statistics were employed in the analysis of data. Findings: The average vaccination rate was 65.3 with the highest rate in nurses (76%), then doctors (64%) and technicians (44%). Threat of disease was the principal driving factor (52.3) and time shortage (48.1) was the major impediment. The level of knowledge was high (97%), and the positive attitude was present. Conclusion: Vaccination coverage is medium and decreasing, with employment differences and logistics. Policies and educational programs are required to be mandatory to enhance uptake.